A Study of ESG Disclosure and Intellectual Capital on Environmental Risk with Sustainable Growth as a Moderating Variable in Big-Cap Multinational F&B Companies - Denaza Putri Rahmadi; Euis Mufahamah; Anita (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the effect of ESG Disclosure and Intellectual Capital on Environmental Risk, with Sustainable Growth as a moderating variable. This research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports of multinational Food & Beverage big-cap companies during the period 2020–2024.The analytical methods used include panel data regression and Moderated Regression Analysis (MRA) with the assistance of EViews software. ESG Disclosure and Intellectual Capital are used as independent variables, Environmental Risk as the dependent variable, and Sustainable Growth as the moderating variable.The results show that ESG Disclosure has a negative and significant effect on Environmental Risk, indicating that higher levels of sustainability disclosure reduce environmental risks. Intellectual Capital does not have a significant direct effect on Environmental Risk. However, Sustainable Growth strengthens the influence of ESG Disclosure and Intellectual Capital on Environmental Risk. In addition, ESG Disclosure and Intellectual Capital simultaneously have a significant effect on Environmental Risk.This study implies that companies need to integrate ESG practices, intellectual capital, and sustainable growth strategies to effectively manage environmental risks and achieve long-term sustainability.